Long-term safety and efficacy of lasmiditan for acute treatment of migraine: Final results of the GLADIATOR study. (14th September 2020) - Brandes, Jan Lewis; Klise, Suzanne; Krege, John H; Case, Michael; Khanna, Rashna; Vasudeva, Raghavendra; Raskin, Joel; Kudrow, David
GLADIATOR was a prospective, randomized, open-label, phase 3 study of lasmiditan 100 mg or 200 mg dosed intermittently for up to 1 year in patients with episodic migraine. Most patients had completed one of two single-attack studies before participation. A total of 2030 patients received ≥1 lasmiditan dose and 19, 879 migraine attacks were treated. Safety results were similar to the previously reported interim analysis. The most frequently reported treatment-emergent adverse events (TEAEs) included dizziness (18.5%), somnolence (8.5%), and paresthesia (6.8%), with frequency of adverse events appearing to decrease with subsequently treated attacks. At 2 h post-dose, 26.7% and 32.2% of all attacks treated with lasmiditan 100 mg and 200 mg, respectively, were pain free. This pattern was generally consistent across study quarters and treated attacks. In conclusion, during a 1-year treatment period, intermittent lasmiditan for episodic migraine treatment was associated with generally decreasing TEAEs and consistent efficacy.